A Suicide Prevention: Literature Review - Soleman, Sitti Rahma; Utomo, Endrat Kartiko (Coping: Community of Publishing in Nursing; Vol 8 No 4 (2020): Desember 2020DO - 10.24843/coping.2020.v08.i04.p08, 2020)
ABSTRACT Suicide is one of the leading causes of death worldwide. Suicide is an intentional act to end life. Pharmacological, psychological, health education, family support and the media are proposed as effective measures to treat depression and suicide. However, these guidelines do not have sufficient evidence to prevent suicide so this is a challenge for the world of health, especially nursing. The aim of this review is to report the results of studies that focus on interventions undertaken for suicide prevention. The search method for relevant articles uses the database PubMed, Science Direct and Google Scholar using the keywords suicide prevention, suicide intervention, and suicide therapy. Nine articles were included in the literature review, covering various types of suicide intervention, frequency of intervention, and effects of intervention. This literature review identifies eight types of interventions that can be done to prevent suicide, namely ACT, CBT, SAFETY, SOS, ASSIP. The conclusion is that ACT, CBT, SAFETY, SOS, ASSIP interventions can be done to prevent suicide, by increasing knowledge, education, skills regarding suicide and awareness related to suicide and family participation are the main points of interventions that must be carried out to prevent suicide . Keywords: Prevention of suicide, suicide intervention, suicide therapy